2019
DOI: 10.1002/ejic.201900032
|View full text |Cite
|
Sign up to set email alerts
|

Phosphophosphidites Derived from BINOL

Abstract: Phosphophosphidites of the type R 2 P-P(binol) [where binol = the dianion of (S)-1,1′-bi-2-naphthol] are the phosphorus analogues of the ubiquitous phosphoramidites, R 2 N-P(binol) and are readily accessed by the chlorosilane elimination reaction between R 2 P-SiMe 3 and Cl-P(binol). The crystal structure of iPr 2 P-P(binol) (1) has been determined and shows a P-P bond length in the normal range. The solution reactions of 1 have been investigated, principally by 31 P NMR spectro- IntroductionHomodiphosphanes Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The coordination chemistry of diphosphanes, especially towards soft metals, has been poorly studied in comparison with tertiary phosphines. Diphosphanes are known to bridge two metals in a μ‐P/P fashion, [9d,24] coordinate through a single P donor atom, [9f,12a,25] or P/P‐chelate forming a three‐membered metallacyclic ring [26] . To probe the bridging ability of P − P(NMe 2 ) we focussed our studies on Pd II and Pt II metal centres.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination chemistry of diphosphanes, especially towards soft metals, has been poorly studied in comparison with tertiary phosphines. Diphosphanes are known to bridge two metals in a μ‐P/P fashion, [9d,24] coordinate through a single P donor atom, [9f,12a,25] or P/P‐chelate forming a three‐membered metallacyclic ring [26] . To probe the bridging ability of P − P(NMe 2 ) we focussed our studies on Pd II and Pt II metal centres.…”
Section: Resultsmentioning
confidence: 99%
“…Both symmetrically and asymmetrically substituted diphosphanes can be synthesized via dehydrocoupling, salt metathesis, and trimethylsilyl chloride (TMSCl or Me 3 SiCl) elimination reactions. A variety of symmetrically as well as asymmetrically substituted diphosphanes have been reported so far, containing B-substituted, , C-substituted, , Si-substituted, N-substituted, ,,,,,,, P-substituted, , O-substituted, S-substituted, and H-substituted , P atoms. Despite this variety, the selective introduction of certain substituents to access diphosphanes with a defined substitution pattern remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“… 19 24 When they react with electrophiles, the P–P bond is either retained, and thus diphosphane acts as a classical P-based nucleophile, or the initial electrophilic attack is followed by cleavage of the P–P bond, which in turn can lead to double phosphination of the activated molecule. 25 28 To date, the vast majority of studies have focused on the diphosphanation of simple unsaturated organic compounds. 29 Miura et al and Sato et al showed that two PR 2 groups add to a double or a triple carbon–carbon bond in alkenes, alkynes, or arynes in either catalyzed or photoinitiated reactions with commercially available Ph 2 P–PPh 2 to give 1,2-bis(diphenylphosphino) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Among many synthetic approaches, metal-free activation of small molecules employing low-valent phosphorus compounds has been of particular interest in recent years. In the vast majority of such reactions, the P center acts as a Lewis base that, either by itself , or in cooperation with a Lewis acidic center in an ambiphilic system, binds to the activated molecule, leading to its functionalization. Reactions employing Lewis bases with P–P bonds are still an unexplored area of research, with the largest portion of reports devoted to the smallest representatives of this groupdiphosphanes. When they react with electrophiles, the P–P bond is either retained, and thus diphosphane acts as a classical P-based nucleophile, or the initial electrophilic attack is followed by cleavage of the P–P bond, which in turn can lead to double phosphination of the activated molecule. To date, the vast majority of studies have focused on the diphosphanation of simple unsaturated organic compounds . Miura et al and Sato et al showed that two PR 2 groups add to a double or a triple carbon–carbon bond in alkenes, alkynes, or arynes in either catalyzed or photoinitiated reactions with commercially available Ph 2 P–PPh 2 to give 1,2-bis­(diphenylphosphino) derivatives. By tailoring the properties of diphosphanes so that the P–P bond is more labile, it is possible to increase the diversity of the PRR′ moieties and provide a more general approach to the straightforward functionalization of the C  C or CC bonds.…”
Section: Introductionmentioning
confidence: 99%